Characteristics and Surgical Success of Patients Presenting for Repair of Genitourinary Fistula in VVF Center of a Tertiary Hospital - Ara, Rowshan; Amin, Abu Taher Mohammad Nurul; Hoque, Md Shadiqul; Kasem, Setara Binte (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): To carry out a prospective review of patients who had undergone surgical repair of genitourinary fistula to determine patients characteristics and to explore success of surgery in relation to aetilogy of fistula and attempt of surgery. Materials and Methods : This cross-sectional study was carried out in patients attending the Fistula centre in Dhaka Medical College and Hospital (DMCH) from April 27th to July25th, 2013. Out of 47 patients 27 were recruited for this study. Detailed history was taken about socio-demographic character, gestational age, duration of labour, mode of delivery, conduction of labour and foetal outcome. Causes of fistula, information about fistula repair and success rate were noted. Main outcome measures were successful repair and correlation of success with aetiology of fistula, attempt of surgery. Data were analyzed by SPSS package. A p value of <0.5 was considered as significant. Results: Mean age of the patients was 33.73± 10.73 years with a range of 17 to 58 years and mean height was 144.67±3.013cm. Most of the women (66.7%) were from lower social class. The most common fistula 19 (70.37%) was obstetric due to obstructed labour and in 8 (25.93%) cases it was due to consequence of gynaecological surgery. Mean gestational age of the foetus were 38.57±1.409 weeks and duration of labour was 34.83±14.618 hours. Out of 27 patients, 7 had prior fistula repair without success, 4 patients had prior 2 attempts and 3 had previous 3 and 4 attempts. In 21 patients surgical repair was done through vaginal route while 6 required abdominal approach. Local repair was done in 18 (66.67%) cases and grafting was done in 5(18.52%) cases. Fifteen (55.56%) patients had successful repair and success rate was more when it was first attempted (90%) and 20% in repeat attempt but it was statistically significant p<0.05. Success of repair was more when causes of fistula was gynaecological (87.50%) than when it was obstetrical (42.11%), p<0.05. Conclusion: Success of surgery of genitourinary fistula depends upon so many factors. Gynaecological fistula can be repaired more successfully than obstetrical one. First attempt of surgery is the best attempt, so must be done at skilled hand. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 34-39